CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

If in the expansion of (1+x)n, the coefficients of pth and qth terms are equal, prove that p+q =n+2, where pq.


Solution

We have,

(1+x)n

Coefficients of pth term =nCp1

and, Coefficients of qth term =nCq1

It is given that, these coefficients are equal.

nCp1=nCq1

p1=q1 or, p-1 +q-1 =n

[nCr=nCsr=s or r+s =n]

pq=0 or, p+q =n+2

p+q=n+2

Hence proved.

flag
 Suggest corrections
thumbs-up
 
0 Upvotes


Similar questions
QuestionImage
QuestionImage
View More...


Same exercise questions
QuestionImage
QuestionImage
View More...


People also searched for
QuestionImage
QuestionImage
View More...



footer-image